ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI TEOREMA PYTHAGORAS - Veni Siswiandini (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
This article is an analysis of the test results of math problem solving questions for class VIII students junior high school. The analysis carried out aims to determine the types of difficulties experienced by students and to determine the level of ability to solve mathematical problems students at the Pontianak City Junior High School. The research method used is qualitative. As for The samples taken for this study were 3 of class VIII students in one of the junior high schools in the city Pontianak. The instrument for testing the ability to solve mathematical problems is given as many as 3 items question. The results of the analysis obtained based on the written tests conducted are the level of ability solving students' mathematical problems in one of the junior high schools in Pontianak City is still relatively low.